Integrating Character Education in Al-Syifa Islamic Boarding Schools: A Case Study Approach - Fajli Aijat Mau (Edu Spectrum: Journal of Multidimensional Education, 2024)
Character education is a crucial aspect of student development, especially in Islamic boarding schools, known as pesantren, where both academic and moral education are emphasized. This study investigates the integration of character education at Al-Syifa Islamic Boarding Schools, aiming to understand the theoretical and practical frameworks used in these institutions. The primary objective of this research is to analyze how character education is integrated into the educational framework of Al-Syifa Islamic Boarding Schools. The study aims to uncover the strategies, principles, and effectiveness of character education programs through an extensive review of existing literature and documented practices. This research employs a literature review approach, systematically examining academic articles, books, official school documents, and previous studies related to character education in Islamic boarding schools. By synthesizing findings from these sources, the study provides a comprehensive overview of the methods and outcomes of character education integration at Al-Syifa. The literature review reveals that Al-Syifa Islamic Boarding Schools employ a multifaceted approach to character education, integrating it through both curricular and extracurricular activities. The curriculum includes dedicated character education subjects, while extracurricular activities reinforce these values through real-life applications and community involvement. The review also highlights several key principles, such as the emphasis on Islamic values, community living, and moral exemplarity. The integration of these principles has shown positive outcomes, including enhanced student behavior, improved academic performance, and stronger community ties. Challenges noted include the need for continuous professional development for teachers and the alignment of character education goals with academic objectives